Bedtime Storytelling: A Method to Enhance Early Childhoods’ Language Development - Mulyono, Nono; Herniawati, Ani; Hidayat, Yusuf (Jurnal Pendidikan Anak Usia Dini Undiksha, 2023)
Psychologically, young children generally enjoy listening to stories told by their parents. This study aims to analyze the impact of storytelling before bed by parents in order to improve early childhood language development. This research uses a qualitative method with a case study approach. The respondents of this study were 15 mothers and 15 children aged 5-6 years. The methods used to collect data were in-depth interviews and observation. Data analysis techniques use qualitative and quantitative descriptive. The results of the research show that storytelling before bed impacts children's fluency in pronouncing words, vocabulary mastery, self-confidence, and creativity in retelling the stories they hear. In conclusion, storytelling before bed can empirically improve children's language development significantly. Apart from that, this research has implications for the teaching and learning process in PAUD units, where teachers are advised to use the storytelling method during the teaching and learning process. Parents are also advised to get into the habit of telling stories before bed as one of the methods used in developing language in early childhood, especially for young children. 5-6 years.